Policy making reform: Command and control within Jordanian governmental institutions - Ali Rawabdeh, Rami Tbaishat, (Opción, 2020)
The intent of this research is to undertake a systematic methodical study of Jordanian governmental administrative improvement and investigate the experiences and characteristics of such a reform. The study revealed that the degree of legitimacy ascribed to both the state and its administrative apparatus is clearly the major factor that can either impede or promote effective levels of accountability and responsiveness. In conclusion, underperformance management, input-oriented budgets are turned into performance budgets, cash-based accounting systems are changed into accrual-based cost accounting systems or performance reporting systems